Boomerang and bones: Refining the chronology of the Early Upper Paleolithic at Obłazowa Cave, Poland. - Sahra Talamo; Nicole Casaccia; Michael P Richards; Lukas Wacker; Laura Tassoni; Adam Nadachowski; Anna Kraszewska; Magda Kowal; Jakub Skłucki; Christopher Barrington; Monica Kelly; Frankie Tait; et al. (PLoS ONE, 2025)
Beginning with the Early Aurignacian, Homo sapiens demonstrated an enhanced symbolic capacity, expanding artistic expressions from body decoration to portable art and aesthetically refined tools. These artistic endeavors, often intertwined with utilitarian purposes, have sparked debates regarding their symbolic versus functional roles. Among these remarkable artifacts is a complete mammoth tusk boomerang from Layer VIII of Obłazowa Cave, Poland, found in association with a human phalanx. Determining its precise chronology and cultural context is critical for understanding the emergence and variability of symbolic behaviors among early Homo sapiens groups in Europe. This study refines the chronology of the Early Upper Paleolithic occupation of Layer VIII at Obłazowa Cave through radiocarbon dating of several bones and the human fossil found near the ivory boomerang. Bayesian modeling places the site's main occupation phase between 42,810-38,550 cal BP (95,4% probability). The mammoth-ivory boomerang, calibrated to 42,290-39,280 cal BP with a 95.4% probability, emerges as one of Europe's oldest known examples of this complex tool, exemplifying technological and symbolic innovation at Obłazowa Cave. This multi-disciplinary research underscores the importance of integrating advanced methodologies to explore cultural practices during the Upper Paleolithic. The findings not only deepen our understanding of Homo sapiens' adaptive strategies but also highlight the nuanced interplay of technology, symbolism, and environmental interaction during the earliest phases of human dispersals in Central Europe.